A note on the parabolic identification problem with involution and Dirichlet condition - Ashyralyev, A.; Erdogan, A.S.; Sarsenbi, A. (Bulletin of the Karaganda University. Mathematics Series, 2020)
A space source of identification problem for parabolic equation with involution and Dirichlet condition is studied. The well-posedness theorem on the differential equation of the source identification parabolic problem is established. The stable difference scheme for the approximate solution of this problem is presented. Furthermore, stability estimates for the difference scheme of the source identification parabolic problem are presented. Numerical results are given.